The Socioeconomic analysis in poultry egg production in Dang valley: The socioeconomic analysis in poultry egg production in Dang valley. - Gautam, Anup (International Journal of Applied Sciences and Biotechnology, 2019)
This study was carried out in Tulsipur sub-metropolitan city and Ghorahi sub-metropolitan city of Dang valley. It was aimed to analyze socioeconomic status of poultry egg producing farms and constraints limiting their operations. A sample size of 60 poultry egg producing farm were selected by simple random sampling technique. Data collected from the pretested questionnaire were analyzed using Statistical Package for Social Science (SPSS) and Microsoft Excel. The result revealed that in Tulsipur sub-metropolitan city the poultry layers farms have mean flock size of 3345 birds and in Ghorahi sub-metropolitan city mean flock size of 3666 was found. An average producer in the farms of Tulsipur sub-metropolitan was 40 and that of Ghorahi sub-metropolitan city was 36 years. The result revealed that majority (83.33%) of poultry layers farms are male dominant in research area, majority (86.66%) of the layers producers belongs to ethnicity brahmin/chhetry, majority (41.66%) of the poultry layers farms owners belongs to SLC level education,majority (90%) of the layers farm owners main occupation is agriculture,  majority (96.66%) of the layers farms in the dang valley are individually owned,majority (95%) of the layers farms do not get any support from government, majority (90%) of the layers farm are found to supply egg regularly and BC ratio of Tulsipur sub-metropolitan and Ghorahi sub-metropolitan city was found to be 1.21 and 1.44 respectively. Based on the findings of the study, it was concluded that the poultry egg producing farms are profitable and they possesses high growth potentials which are achievable through increased investment and proper management of identified constraints. Int. J. Appl. Sci. Biotechnol. Vol 7(2): 289-290